Radio's Civic Ambition: American Broadcasting and Democracy in the 1930s. - Godfried, Nathan (Journal of American History, 2011)
The article reviews the book "Radio’s Civic Ambition: American Broadcasting and Democracy in the 1930s," by David Goodman.